2022
DOI: 10.1039/d2gc03187f
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light-induced sulfonylarylation of unactivated alkenes via 1,4-(hetero)aryl migration from oxygen or nitrogen to carbon

Abstract: Migration of a remote aryl group is a state-of-the-art strategy for difunctionalization of alkenes strategy. Herein, we report a method for visible-light-induced sulfonylarylation reactions of unactivated alkenes via 1,4-(hetero)aryl migration...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Based on the above experiments and reference-related literature (Figure ), , we proposed a feasible reaction mechanism in Figure . Eosin Y changes from a ground state to an excited state after Eosin Y absorbs light energy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the above experiments and reference-related literature (Figure ), , we proposed a feasible reaction mechanism in Figure . Eosin Y changes from a ground state to an excited state after Eosin Y absorbs light energy.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported visible light-triggered heteroaryl migration/desulfonylation reaction by using teteroarylalkenes and thiosulfonate . Afterward, Wang et al and Wang et al reported similar reactions. These strategies are good to achieve the dual function of unactivated olefins.…”
Section: Introductionmentioning
confidence: 99%
“…The authors have cited additional references within the Supporting Information. [24][25][26][27][28]…”
Section: Supporting Informationmentioning
confidence: 99%
“…Organic photoredox catalysis is a green, mild, and highly efficient synthetic tool, which has been applied to the construction of carbon–carbon and carbon–heteroatom bonds . Even though some alkenes can undergo cascade distal arylation migration with radicals via organic photocatalysis, such as trifluoro radicals, sulfonyl/sulfinyl radicals, fluorine-containing radicals, arylphosphonyl/acyl radicals, etc., little attention has been paid to organic photoredox silyl-mediated aryl/alkenyl migration of unactivated alkenes. With our continuous efforts in photomediated construction of carbon–silicon bonds by the addition of silyl radicals to unsaturated chemical bonds with hydrosilanes, we envisioned that, under the right set of conditions, silyl-mediated (hetero)­aryl/alkenyl migration reactions could be processed after the addition of silyl radicals to unactivated alkenes bearing (hetero)­aryl/alkenyl amines, enabling the simultaneous incorporation of silyl and (hetero)­aryl/alkenyl groups to alkenes, which would be beyond the well-established synthesis of organosilicon compounds.…”
mentioning
confidence: 99%